Implementation of Internal Quality Guarantee System to Increase the Quality of Education in Junior High School 21 Malang - Ika Rahmania; Budiono Budiono; Siti Fatimah Soenaryo; Abd. Syakur; Agus Tinus (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this study is to examine the implementation of SPMI, examine the results of the implementation of SPMI and examine the factors inhibiting the implementation of SPMI in Junior High School 21 Malang as an effort to improve the quality of education. Primary data were obtained from the SPMI implementers, namely the school principal, supervisors and the quality assurance team at Junior High School 21 Malang. Secondary data were obtained from references, books and documents related to the implementation of SPMI. Data analysis techniques used in this study consisted of three stages, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of SPMI in Junior High School 21 Malang is documented from 2016 to 2019. The implementation of SPMI involves all components of the school from top to bottom. The implementation of SPMI begins with quality mapping, quality fulfillment planning, implementation of quality fulfillment, evaluation and standard setting is proceeding well. The successful implementation of SPMI has increased as evidenced by graduates in 2019 getting 4th place on the results of the Computer-Based National Examination (UNBK). Implementation of quality has become a culture and character that influences the quality of graduates of Junior High School 21 Malang.